GROWTH AND PRODUCTION OF MINI ELEPHANT GRASS IN POST-MINING LAND THAT IS FERTILIZED WITH MANURE - V., VINANDA; SYARIFUDDIN, N. A.; SUMANTRI, I (Majalah Ilmiah Peternakan, 2024)
Mini elephant grass is a forage for livestock that has high production and nutritional quality. Post-coal mining land is land that has a very low fertility rate. This study aims to determine the optimum dose of cow manure for the growth and production of mini elephant grass in post-coal mining land. This research was carried out in the post-mining area of PT Arutmin Indonesia Site Satui. This study used a completely randomized design with four treatments and five replications. The experimental treatment was a cow manure dose of 0 tons/ha (control) (P0), 5 tons/ha (P1), 10 tons/ha (P2), and 15 tons/ha (P3). The variables observed were plant height, number of tillers, leaf length, and production of fresh and dry matter. The data obtained were analyzed using the SPSS Ver.21 program. The application of cow manure significantly (P<0,05) increased the growth and production of mini elephant grass in post-coal mining land. The optimum dose of cow manure to increase the growth and production of mini elephant grass in post-mining land is 10 tonnes/ha which will produce 16.46 tillers per clump, plant height 52.33 cm, leaf length 49.33 cm, fresh forage production 2.4 tons/ha and dry matter production 0.53 tons/ha.